2020
DOI: 10.2196/19180
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Symptom Management System for Patients with Malignant Pleural Mesothelioma (ASyMSmeso): Mixed Methods Study

Abstract: Background Patients with malignant pleural mesothelioma (MPM) have a life-limiting illness and short prognosis and experience many debilitating symptoms from early in the illness. Innovations such as remote symptom monitoring are needed to enable patients to maintain wellbeing and manage symptoms in a proactive and timely manner. The Advanced Symptom Management System (ASyMS) has been successfully used to monitor symptoms associated with cancer. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(51 citation statements)
references
References 29 publications
1
50
0
Order By: Relevance
“…ASyMS was associated with statistically significant improvements in anxiety. Our findings may differ from relatively small post-intervention effects on psychological symptoms reported in literature pertinent to routine use of patient reported outcome measures43; however, they are consistent with earlier studies of ASyMS in which participants reported feelings of enhanced safety and reassurance 20212344. Anxiety is the most common psychological symptom after a diagnosis of cancer and is higher among people with cancer than in the general population,4546 so these effects may benefit a large proportion of oncology patients; however, this needs to be confirmed in future studies.…”
Section: Discussionsupporting
confidence: 79%
“…ASyMS was associated with statistically significant improvements in anxiety. Our findings may differ from relatively small post-intervention effects on psychological symptoms reported in literature pertinent to routine use of patient reported outcome measures43; however, they are consistent with earlier studies of ASyMS in which participants reported feelings of enhanced safety and reassurance 20212344. Anxiety is the most common psychological symptom after a diagnosis of cancer and is higher among people with cancer than in the general population,4546 so these effects may benefit a large proportion of oncology patients; however, this needs to be confirmed in future studies.…”
Section: Discussionsupporting
confidence: 79%
“…eHealth technology was recognised for its ability to help develop new or build upon existing relationships with healthcare providers, family members and peers diagnosed with cancer. Symptom reporting technologies promoted a belief that participants with cancer were working in collaboration with their healthcare team and appreciated the transparent dialogue regarding their experience and care needs (Högberg et al, 2015;Gustavell et al, 2020;Maguire et al, 2020;McCann et al, 2009;Mirkovic et al, 2014). This sense of connection was also evident in Moshen and colleagues' ( 2021) study of people with cancer and their access to education and personal medical information using eHealth technology.…”
Section: Connection and Collaboration With Healthcare Professionals Family And Peersmentioning
confidence: 93%
“…Some partners of people with breast cancer referred to it as an obligation which could invoke guilt if they did not complete their assigned activities. Conversely, other studies found that technology was easily embedded in their daily routine and personal schedule (Maguire et al, 2020;Ngo et al, 2020;Hauffman et al, 2020), appreciating the option to engage at a time and pace that suited them (Song et al, 2015;Smith et al, 2020a;Drott et al, 2016) and enabled the person with cancer to plan their schedule (Mohsen et al, 2021;Crafoord et al, 2020). Participants with cancer also found benefit from eHealth technology in that they gained time in their own lives and did not have to travel to their treatment centre for supportive care, whereby people with cancer perceived an additionalreduced burden on their family caregivers (Dalby et al, 2021;Ownsworth et al, 2020).…”
Section: Alignment and Integration Of Ehealth Technology Into Daily Lifementioning
confidence: 95%
See 2 more Smart Citations